2018
DOI: 10.1051/matecconf/201821402002
|View full text |Cite
|
Sign up to set email alerts
|

Neural Networks and the Philosophy of Dialectical Positivism

Abstract: The fact that the theory of neural networks permits the completeness of the concept of global evolutionism has been shown. This concept in the current philosophical literature is seen, inter alia, as an effective platform for interdisciplinary cooperation, the need for which is becoming more acute, which is reflected in the anniversary report of the Club of Rome in the form of the thesis on the "New Enlightenment". The theory of neural networks allows us to give a consistent interpretation of the category of "… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…This issue is not only of highly specialized interest, but also has a direct bearing on the problem of the essence of intelligence. Recently we report [10], [11] that the intellect should first of all be considered as a kind of information processing system. It was also emphasized there that all discussions regarding which systems can be attributed to artificial intelligence, and which cannot, should be considered pointless, as long as the essence of intelligence as such remains undisclosed.…”
Section: Research Methods 21 Comparison Of Neural Network With Electronic Circuits Based On Logical Elementsmentioning
confidence: 99%
See 1 more Smart Citation
“…This issue is not only of highly specialized interest, but also has a direct bearing on the problem of the essence of intelligence. Recently we report [10], [11] that the intellect should first of all be considered as a kind of information processing system. It was also emphasized there that all discussions regarding which systems can be attributed to artificial intelligence, and which cannot, should be considered pointless, as long as the essence of intelligence as such remains undisclosed.…”
Section: Research Methods 21 Comparison Of Neural Network With Electronic Circuits Based On Logical Elementsmentioning
confidence: 99%
“…Accordingly, the question of what can be considered the memory of neural networks, from the point of view of a consistent scientific methodology, today de 511 connection with the problem of the essence of intelligence [10], [11]. Indeed, if we consider a neural network with a concrete set of weight coefficients, then, strictly speaking, there is no need to talk about its memory at all.…”
Section: Introductionmentioning
confidence: 99%
“…At this stage, the authors identified the main components of the interpretation process: the cultural context of the era, the artistic styles of modernism and postmodernism, within which the ballet was inerpreted; the specifics of the author's creativity; understanding a work of art as an element of the author's text system; known interpretations, their evolution and relationship; methods and "techniques" of interpretation as logical reconstruction of the original. Each significant element was considered independently of the others, and their interaction was determined by the cumulative effect Suleimenov et al, 2018). At the same time, outside data were recorded.…”
Section: Methodsmentioning
confidence: 99%
“…It has relative independence (its own developmental logic); supporters of this theory may die, but new ones continues to live, etc. (Suleimenov, Massalimova, Bakirov, & Gabrielyan, 2018). Any natural language which is a selforganizing system that develops according to its own laws, is indirectly associated with aspirations of individuals.…”
Section: Methodsmentioning
confidence: 99%